Complications and Management of Myocardial Infarction in Hypertensive Patients: A Review - Gani, Azhari; Hayati, Kemala (Journal of Syiah Kuala Dentistry Society, 2024)
Background: Myocardial infarction (MI) and hypertension are cardiovascular conditions that frequently coexist and influence each other. Hypertension not only increases the risk of MI but also complicates its clinical management. Therefore, it is crucial to understand the complications arising from this condition and the effective management strategies. Objectives: This systematic review aims to identify and analyze common complications in hypertensive patients experiencing MI and evaluate the optimal management approaches based on the latest literature. Methods: A literature search was conducted in electronic databases such as PubMed, Scopus, and Google Scholar using relevant keywords like "myocardial infarction," "hypertension," "complications," and "management." Articles published in the last five years were selected to ensure the most current information. Inclusion criteria included observational studies, clinical trials, and systematic reviews relevant to the topic. Data were extracted and analyzed descriptively. Results: Of the 1500 articles identified, 45 studies met the inclusion criteria. Major complications found in hypertensive patients with MI included heart failure, arrhythmias, stroke, and left ventricular dysfunction. The most effective management approaches included appropriate use of antihypertensive medications, early reperfusion interventions, and a multidisciplinary approach to controlling cardiovascular risk factors. The use of ACE inhibitors, beta-blockers, and aldosterone antagonists proved to have significant benefits in reducing morbidity and mortality. Conclusions: Complications of myocardial infarction in hypertensive patients require comprehensive and coordinated management. Effective management involves a combination of pharmacological and non-pharmacological therapies focusing on optimal blood pressure control and prevention of further complications. Further research is needed to explore more specific and personalized management strategies in this population.